A Literature Review on Gamification as an Interactive Approach in Mathematics Learning for Elementary School Students - Mursalin, M; Saputra, Eri; Ali, Muhammad (International Journal of Trends in Mathematics Education Research, 2024)
Students' interest and involvement in mathematics learning, particularly at the elementary school level, is often low due to the nature of the material that is considered difficult and less interesting. The gamification approach, which integrates elements of play into learning, emerges as a potential strategy to increase students' motivation and understanding of mathematical concepts. This study aims to analyze the effectiveness of gamification in increasing learning interest and understanding of mathematics in elementary school students. This literature review was carried out by collecting, filtering, and analyzing various relevant previous research, using keywords such as "gamification", "elementaryschool mathematics learning", "student motivation", "educational technology", and "student collaboration". The results of the study show that the application of gamification in mathematics learning has a significant positive impact on student motivation and engagement, improves understanding of mathematical concepts, and facilitates collaborative skills. The implication of these findings is that educators should consider integrating technology-based gamification in the math curriculum, in order to create a learning experience that is more adaptive and relevant to students' needs.